The Creation, Importance and Economic Benefits of Industrial Clusters for Serbian Companies - Radulovic, Miroslav (2008)
This is the first study of industrial clusters in Serbia ever. The aim of this study is to gather information regarding companies, clusters and process of cluster development in Serbia. Having in mind cultural and historical context of the business environment within clusters are working, it was interesting examining what kind of attitude Serbian companies have towards competition, development and important business topics. The main goals of this research is to examine and explore are: 1.) How do clusters form in Serbian economy; 2.) What motivates clustering in Serbia; 3.) What is Serbian Government's approach to clusters; 4.) How does clustering influence local economy, suppliers and buyers; 5.) How is it helping in developing and branding a region; and 6.) What are the implications of clustering on Serbian small and medium enterprises and Serbian market. In order to create comprehensive study, both quantitative and qualitative research methods have been implemented. Therefore, the quantitative research consists out of questioner divided into 18 questions. In total 33 companies have been surveyed in 5 Serbian clusters gaining for the first time valuable answers regarding companies who joined clusters and the expectations and aspirations of cooperation within cluster. Qualitative research has been conducted through 7 in-depth interviews with relevant cluster members and supporting organization members, who's answers will be utilized in order to gain a full picture of the companies, clusters and processes of clustering in Serbia. The study came across interesting conclusions, initially Serbian companies did not start cooperating because they were all aware of the benefits clusters are offering, but they grouped out of need to overcome some of the common legal and business problems. Majority of the companies within clusters are micro and small companies, without research and development. This study showed that even clusters in Serbia do not have R&D division, leading us to the conclusion that companies need to improve knowledge management in the companies, to support innovations and invest in new material and products development. Serbian clusters could play a key role in national economy revitalization, if government recognised entrepreneurship and small and medium companies as a driving force of economy.